Pengenalan Permainan Tradisional di SDN Grujukan 1 Bondowoso sebagai Upaya Mengurangi Kecanduan Gadget - Rifki Adiansah; Ahmad Tajudin Farhan; Shetty Yuke Marchawwalia Nafisa; Indriyana Rohmadani; Muhammad Alvin Nur Hidayat Chabibullah; Sinta Qomariyah Putri; Putu Ucca Pandya Widyadhana Primiardi; Muhammad Ghufron Rosyady; Dwi Erwin Kusbianto; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The use of digital devices has increased rapidly in the digital era, particularly among elementary school-age children. Excessive use of digital devices can influence changes in children's behavior, attitudes, and emotional conditions. The social project aims to provide education about the negative and positive impacts of digital device usage and introduce traditional games as an enjoyable alternative activity for students. The program was conducted at SDN Grujukan 1 Bondowoso, involving 46 students from grades I–VI through counseling methods and direct practice of traditional games, such as Gobak Sodor, which received enthusiastic responses during implementation. Pre-test results showed that only 45% of students understood the impacts of digital device usage correctly. After material delivery and direct practice, there was a significant increase in post-test results, with 85% of students demonstrating understanding of digital device usage impacts and familiarity with the introduced traditional games. The program is expected to help students balance digital device usage with healthier activities and rekindle their appreciation for local culture through traditional games.